2018
DOI: 10.1021/acsearthspacechem.8b00083
|View full text |Cite
|
Sign up to set email alerts
|

Springtime Bromine Activation over Coastal and Inland Arctic Snowpacks

Abstract: With the return of sunlight in the polar spring, the snowpack serves as an effective source of molecular halogens to the Arctic boundary layer. Reactive bromine production and associated ozone depletion are typically associated with sea ice regions; however, the extent to which halogen chemistry occurs inland in coastal regions is unknown. During the March 2012 bromine, ozone, and mercury experiment (BROMEX), airborne nadir scanning differential optical absorption spectroscopy probed the spatial distribution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 70 publications
1
39
0
Order By: Relevance
“…The Br -/Clratios presented in Figure 5 suggest the ability of terrestrial and MYI snowpacks to produce Br 2 should be accounted for in models. Airborne measurements of BrO 200 km inland by Peterson et al (2018) provide further evidence of the effectiveness of terrestrial snowpacks in producing reactive bromine. Given that the conditions for Br 2 production are most frequently observed in terrestrial snowpacks, it is likely those snowpacks will play an increasing role in Arctic boundary layer bromine chemistry as sea ice extent declines.…”
Section: Recommendations For the Modeling Communitymentioning
confidence: 95%
“…The Br -/Clratios presented in Figure 5 suggest the ability of terrestrial and MYI snowpacks to produce Br 2 should be accounted for in models. Airborne measurements of BrO 200 km inland by Peterson et al (2018) provide further evidence of the effectiveness of terrestrial snowpacks in producing reactive bromine. Given that the conditions for Br 2 production are most frequently observed in terrestrial snowpacks, it is likely those snowpacks will play an increasing role in Arctic boundary layer bromine chemistry as sea ice extent declines.…”
Section: Recommendations For the Modeling Communitymentioning
confidence: 95%
“…Domine et al (2004) estimate that frost flowers could account for 10 % of the observed surface snow salinity. The upward migration of brine is expected to be the dominant source of salinity for thin snow over sea ice (< 10-17 cm; Domine et al, 2004;Peterson et al, 2019). As the snow depth gets thicker, the salinity of surface snow decreases and the influence of atmospheric deposition likely becomes more important (Krnavek et al, 2012;Nandan et al, 2017).…”
Section: The Blowing-snow Ssa Simulation In Geos-chemmentioning
confidence: 99%
“…Although there are studies which try to model BrO plumes from their driving mechanisms (Falk and Sinnhuber, 2018;Seo et al, 2019b;Huang et al, 2020), the exact level of impact of each parameter on the formation of enhanced tropospheric BrO is uncertain. However, there is the general consensus that the potential sources of BrO plumes are (a) rich in sea salts and relatively cold (conditions occurring in potential frost flowers regions; Rankin et al, 2002;Kaleschke et al, 2004;Sander et al, 2006), (b) surfaces covered with liquid or frozen brine (Sander et al, 2006), (c) associated with blowing snow (Yang et al, 2008;Blechschmidt et al, 2016;Frey et al, 2020), and (d) surface snow packs (Pratt et al, 2013;Peterson et al, 2018) and young salty sea ice regions (Wagner et al, 2001;Simpson et al, 2007;Peterson et al, 2016). A pH lower than 6.5 is required for efficient bromine activation (Fickert et al, 1999;Halfacre et al, 2019).…”
Section: Time Seriesmentioning
confidence: 99%